PD-L1+ regulatory B cells act as a T cell suppressor in a PD-L1-dependent manner in melanoma patients with bone metastasis. (March 2020) - Wu, Hao; Xia, Liming; Jia, Dongdong; Zou, Hanhui; Jin, Gu; Qian, Wenkang; Xu, Haichao; Li, Tao
Highlights: Level of PD-L1 by circulating B cells was positively associated with tumor stage. PD-L1 + B cells exhibited a naive B cell-like phenotype. Stage III and stage IV melanoma patient naive B cells suppressed T cell response. The suppression was in a PD-L1-dependent manner. The level of PD-L1 + B cells was higher in bone metastases than in the primary tumors. Abstract: The five-year survival rate of melanoma worsens significantly with advancing tumor stage. We hypothesized that regulatory B cells (Breg) might have participated in the pathogenesis of melanoma. In this study, the PD-L1 + Breg cells were investigated. The expression of PD-L1 by circulating B cells was very low in healthy controls. In melanoma patients, on the other hand, the expression of PD-L1 by circulating B cells was significantly elevated in a manner that was positively associated with tumor stage, with the highest level in stage IV bone metastasis patients. Compared to total B cells, PD-L1 + B cells presented higher IgM and higher IgD expression, and were almost exclusively CD20 + CD27 −, suggesting that the PD-L1 + B cells exhibited a naive B cell-like phenotype. Healthy naive B cells, which presented little PD-L1, and stage I and stage II melanoma patient naive B cells, which presented detectable but low PD-L1, were unable to suppress T cell response. However, stage III and stage IV naive B cells, which presented moderate PD-L1, could significantly suppress T cell response in a PD-L1-dependent manner. We further found that the level of PD-L1 + B cells was significantly higher in bone metastasis than in the primary tumors. Overall, we demonstrated that PD-L1 + B cells were upregulated in advanced melanoma and were enriched in metastasis compared to primary tumors. Furthermore, PD-L1 + naive B cells could act as a T cell suppressor in a PD-L1-dependent manner.